Pengembangan Media Pembelajaran Aplikasi Ular Tangga Berbasis Digital pada Pembelajaran IPAS Kelas V Sekolah Dasar - Kinanti Paramuditha, Elvin; Hakim, Lukman; Sri Nindiati, Dina (Edukasiana: Jurnal Inovasi Pendidikan, 2025)
This study aims to develop a digital-based learning media in the form of a snakes and ladders application for the Social and Natural Sciences (IPAS) subject, specifically on the topic of "The Arrival of the Dutch in Indonesia," for fifth-grade elementary school students. The research employed a Research and Development (R&D) method using the ADDIE development model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. Data collection techniques included observation, documentation, questionnaires, and learning outcome tests. The validation results indicated that the developed media is highly valid, with average expert scores of 90% (media expert), 91% (subject matter expert), and 88% (language expert). Practicality tests involving student responses from one-on-one trials, small group trials, and teacher questionnaires yielded scores of 93%, 93%, and 89% respectively, all categorized as “very practical.” Effectiveness was measured through a learning outcomes test with 16 students, showing an average N-Gain score of 0.73, classified as “high” or “very effective.” It can be concluded that the digital snakes and ladders learning application is valid, practical, and effective for use in fifth-grade IPAS learning activities, especially at SD Negeri 32 Prabumulih.